Design of low-rise buildings from thin-walled steel frame structures - Umnova Olga; Tuev Dmitry; Giyasov Timur (MATEC Web of Conferences, 2018)
Addressing sustainable development challenges, Russia is seeking new opportunities for the use of thin-walled cold-cast structures to meet the requirements of cost-effectiveness, eco-friendliness, and rapid construction. The study aims to explore the possibilities of design and calculation of low-rise buildings erected from lightweight thin-walled steel structures using frame construction technology. The design solutions for the roof, walls, floors, and foundation are exemplified using concrete examples. The load capacity off framing studs, roof beams, and floor slabs was calculated. Three methods were used for calculation - Eurocode 3, direct strength test, and ultimate load test in compliance with AISI standards.